Towards the Heart of Teacher Leadership: Collaboration Experiences in Times of Covid-19 - Herrera-Seda, C (EDICIONES UNIV VALPARAISO, 2024)
Teacher Leadership has received attention from educational research due to its relevance for school improvement. Even without agreement on its definition, its collective nature has been emphasised and considered its highly context -dependent. Therefore, expanding teacher leadership conceptualisation is necessary. Using the lens of teachers work, we propose to enrich the teacher leadership definition by focusing on collaboration. With this aim, we characterised teacher collaboration during the pandemic in five Chilean schools, following the following questions: How did the work between teachers occur during the COVID-19 crisis school closures? What tensions did teacher collaboration experience as teachers sought to mobilize change in their diverse contexts? How can analysis of teachers collaboration experiences contribute to broadening perspectives on teacher leadership? A mixed convergent -parallel design was used to conduct the research, which allowed for a deeper understanding of the teaching initiatives and the context in which they took place. The research involved five schools in Santiago de Chile with different dependencies (public, private, and subsidised), and primary and secondary teachers of different disciplines participated in each institution. An individual questionnaire registers collective initiatives of change led by teachers, and a group interview provides a general landscape of work during the crisis. Data processing included qualitative content analysis and the construction of epistemic networks with the information provided by the questionnaire, as well as thematic analysis of the interviews. The findings showed various collective initiatives developed collectively, mainly for crisis adaption and, to a lesser extent, mobilising profound transformations. Teachers initiatives enabled them to learn from each other, reorganise their work, support and care for each other, diversify teaching and promote learning, maintain and strengthen links with students and their families, and rethink the curriculum and education. On the other hand, we identified several tensions in collaboration between teachers, including that teacher -led initiatives in a school are related to the material conditions and demand for formal spaces for joint work. Likewise, we observe that recognising the value of teaching work, constructing a democratic work culture, and teacher autonomy are fundamental elements for teachers to become involved in change processes. Finally, we described the contributions of teachers collaboration experiences to broaden perspectives on teacher leadership. In this regard, we highlight that placing collaboration at the heart of leadership challenges us to delve deeper into the affective dimension of teachers work and to understand the intended and unintended change processes. Also, these experiences showed the interweaving of the dimensions of work, collaboration and teacher leadership. Intertwining these categories invites us to establish conceptual bridges and explore new methodological paths that allow us to rethink leadership and collaboration in different educational contexts in which they emerge.